"Biodiversity Offsetting" in Uganda's Protected Areas: A Pathway to Restoration of Forest Biodiversity? - Kigonya, Ritah; Byakagaba, Patrick; Ssenyonjo, Edward; Nakakaawa Jjunju, Charlotte (Environmental Management, 2024)
With limited national financing for conservation, there is an increasing interest in using biodiversity offset funds to strengthen protected area management. Offsetting measures can potentially be used in the restoration of degraded protected areas. However, there are concerns related to the uncertainty of restoration outcomes and time-lags before the expected benefits can be observed. Using a case of the Gangu Central Forest Reserve in central Uganda, we contribute empirical findings showing the potential and limitations of biodiversity offsetting by means of the restoration of a degraded forest reserve. We use forest cover change analysis and community surveys to determine forest changes after eight years of offset implementation, and forest inventories to analyse the current forest structure and composition to ascertain taxonomic diversity recovery. The results revealed that biodiversity offsetting led to a 21% increase in Tropical High Forest cover, and enhanced restoration of forest species composition and diversity. However, attaining permanence of the restoration benefits requires the regulation of community forest resource access and use. Strengthening forest management capacity to monitor the offset sites and compensating impacted communities for foregone forest resource benefits are crucial for the successful implementation of biodiversity offsets.